Rancang Bangun Alat Monitoring Kerusakan Lampu Penerangan Jalan Umum Berbasis Mikrokontroler dengan Notifikasi SMS - I Gede Andhika Putra; Anak Agung Ngurah Amrita; I Made Arsa Suyadnya (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2018)
Public street lighting is part of a complementary road that serves to illuminate streets at night. Public street lighting lamps are generally operated throughout the night until early morning continuously without equipped tools that monitor conditions. The non-functioning of public street lighting is often not known by officers. In this study, a microcontroller-based damage monitoring tools was built with an SMS-based notification service. This tool is suitable to be implemented to monitor the state of public street lighting because it can monitor the state of lights during the day, lights go out and dim at night, and also can check the state of the lights by sending commands via SMS service. By sending the